Glycine and GABAA receptors mediate tonic and phasic inhibitory processes that contribute to prepulse inhibition in the goldfish startle network - Curtin, Paul C. P.; Preuss, Thomas (Frontiers in Neural Circuits, 2015)
Prepulse inhibition (PPI) is understood as an inhibitory process that attenuates sensory flow during early stages (20-1000ms) of information processing. Here, we applied in vivo electrophysiology and pharmacology to determine if prepulse inhibition (PPI) is mediated by glycine receptors (GlyRs) and/or GABAA receptors (GABAARs) in the goldfish auditory startle circuit. Specifically, we used selective antagonists to dissect the contributions of target receptors on sound-evoked postsynaptic potentials (PSPs) recorded in the neurons that initiate startle, the Mauthner-cells (M-cell). We found that strychnine, a GlyR antagonist, disrupted a fast-activated (5 ms) and rapidly (< 50ms) decaying (feed-forward) inhibitory process that disrupts PPI at 20 ms prepulse/pulse inter-stimulus intervals (ISI). Additionally we observed increases of the evoked postsynaptic potential (PSP) peak amplitude (+87.43 ± 21.53%; N=9) and duration (+204 ± 48.91%, N=9). In contrast, treatment with bicuculline, a GABAAR antagonist, caused a general reduction in PPI across all tested ISIs (20-500 ms), essentially eliminating PPI at ISIs from 20-100 ms. Bicuculline also increased PSP peak amplitude (+133.8 ± 10.3%, N=5) and PSP duration (+284.95 ± 65.64%, N=5). Treatment with either antagonist also tonically increased post-synaptic excitability in the M-cells, reflected by an increase in the magnitude of antidromically-evoked action potentials (APs) by 15.07 ± 3.21%, N=7 and 16.23 ± 7.08%, N=5 for strychnine and bicuculline, respectively. These results suggest that GABAARs and GlyRs are functionally segregated to short- and longer-lasting sound-evoked (phasic) inhibitory processes that contribute to PPI, with the mediation of tonic inhibition by both receptor systems being critical for gain control within the M-cell startle circuit.